Advanced Frequency Synthesis by Phase Lock - Egan, William F., 1936- (Hoboken, New Jersey : John Wiley & Sons, 2011)
'An addendum to the popular Frequency Synthesis by Phase Lock, 2nd ed, this book describes sigma-delta, a frequency synthesis technique that has gained prominence in recent years. In addition, Simulink will be employed extensively to guide the reader. Fractional-n, the still-used forerunner to sigma-delta, is also discussed. Sequences of simulated results allow the reader to gain a deeper understanding while detailed appendices provide information from various stages of development. Simulation models discussed in the chapters that are available online'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Frequency synthesizers; Phase-locked loops